Modulation of membrane lipid raft by omega-3 fatty acids and possible functional implication in receptor tyrosine-kinase activation - Sottocornola, E.; Berra, Bruno (Progress in Nutrition, 2008)
Current understanding of biologic membrane structure and function is largely based on the concept of lipid rafts. Lipid rafts are composed primarily of tightly packed, liquid-ordered sphingolipids/cholesterol/saturated phospholipids that float in a sea of more unsaturated and loosely packed, liquid-disordered lipids. Lipid rafts have important clinical implications because many important membrane-signalling proteins are located within the raft regions of the membrane, and alterations in the raft structure can alter the activity of these signalling proteins. Because rafts are lipid-based, their composition, structure, and function are susceptible to manipulation by dietary components such as omega-3 polyunsaturated fatty acids and by cholesterol depletion. Important components of lipid rafts are receptor tyrosine-kinase, such as the ErbB receptor superfamily. Here we review how alteration of raft lipids affects the raft/nonraft localization and hence the function of several proteins involved in cell signalling, focusing our discussion on two members of the ErbB receptors: EGFR and ErbB2, that are specifically involved in the development of many solid tumors, such as mammary adenocarcinomas.